A Comparative Analysis of the Duration and Cost of Treatment Between Glass Ionomer and Resin Based Fissure Sealants among Children in Benin City, Nigeria - P.U. `; E.O. Sote; F.A. Oredugba; I.N. Ize-Iyamu (Nigerian Dental Association, 2020)
Background: Dental service utilization in children is reduced as a result of long treatment times and prohibitive cost of treatment. This may result in  an increase in early childhood caries and subsequent premature tooth loss. Fissure sealants are a preventable method in the management of  dental caries but the cost may be a barrier to early treatment. Aim: To compare the duration and cost of sealant treatment between glass ionomer and resin based fissure sealants among children in Benin City, Nigeria. Materials and Methods: All occlusal surfaces of the lower permanent first molars (2 teeth each in a total number of 50 children) were sealed and included in the study (n=100). A split-mouth design was used in which a light cure Bis-GMA resin-based sealant was compared with a glass-ionomer sealant. They were then randomly placed in 50 matched contralateral pairs of permanent first molar teeth and a stop watch used to record the duration of placement. The cost of treatment was calculated by dividing the cost of the sealant kit with the total number of sealed occlusal surfaces. Statistical analysis was done using Statistical Package for Social Sciences version 21.0 with the chi square test for determination of variables. Probability values of p<0.05 were considered statistically significant. Results: The duration of sealant treatment using resin based sealant ranged from 235 to 446 seconds (mean time 318.86 +55.54 secs); while the duration of sealant treatment using glass ionomer based sealant ranged from 238 to 360 seconds (a mean time 292.57 +33.56 secs); and this was statistically significant (P<0.001). The cost of sealing a tooth surface using resin sealant (Clinpro®) was five hundred and seventy naira only. Similarly, the cost of sealing a tooth surface using glass ionomer based sealant (GC Fuji triage®) was eight hundred and forty naira only. Conclusion: Less chairside time is required for sealant treatment using glass ionomer than resin based sealant for fissure sealing procedures. The use of resin based fissure sealant is relatively cheaper when compared with glass ionomer based sealant